Dipeptidyl Peptidase 4 Inhibitors Decrease the Risk of Hepatocellular Carcinoma in Patients With Chronic Hepatitis C Infection and Type 2 Diabetes Mellitus: A Nationwide Study in Taiwan - Hsu, Wei-Hao; Sue, Shu-Ping; Liang, Hsiu-Ling; Tseng, Chin-Wei; Lin, Hsiu-Chu; Wen, Wei-Lun; Lee, Mei-Yueh (Frontiers in Public Health, 2021)
Introduction: Dipeptidyl peptidase 4 inhibitors (DPP-4 inhibitors) are incretin-based oral antidiabetic drugs. Previous studies have shown an association between increased plasma activity of DPP-4 and chronic hepatitis C virus (HCV) infection. Dipeptidyl peptidase 4 inhibitors may be associated with preventing the development of chronic HCV infection. The aim of this study was to investigate whether the use of DPP-4 inhibitors is associated with a decreased risk of hepatocellular carcinoma (HCC) in patients with diabetes mellitus (DM) and chronic HCV infection. Methods: In this retrospective cohort study, we enrolled patients with type 2 diabetes and chronic HCV infection from the National Health Insurance Research Database (NHIRD) in Taiwan. The patients were divided into two groups (DPP-4 inhibitor cohort and non-DPP-4 inhibitor cohort) according to whether or not they received DPP-4 inhibitor treatment. Results: Multivariate Cox proportional hazard regression analysis showed a significantly lower risk of HCC in the patients who took DPP-4 inhibitors compared to those who did not. Kaplan-Meier survival analysis demonstrated a significantly higher HCC-free rate in the DPP-4 inhibitor cohort than in the non-DPP-4 inhibitor cohort. Conclusion: The use of DPP-4 inhibitors was associated with a lower risk of HCC in patients with type 2 DM and chronic HCV infection.